What drives the declining wealth effect of subsequent share repurchase announcements? - David K. Ding; Hardjo Koerniadi; Chandrasekhar Krishnamurti (Journal of Risk and Financial Management, 2020)
Recent academic studies document that open market share repurchase announcements in the United States generate significantly lower returns than those reported in earlier studies. We find that the lower announcement return is associated with an increasing number of subsequent announcements in the more recent periods. Although the announcement period return from the initial announcement is positive, subsequent announcement returns are significantly decreasing. Further, we find that the decreasing returns of subsequent announcements are attributed to firms with negative past repurchase announcement returns. Our multivariate regression test results are consistent with the notion that the decreasing subsequent repurchase announcement returns are driven by hubris-endowed managers.
Keywords: 330; cumulative announcement returns; endowed; hubris; open market share repurchase